Retrospective Examination of Vessel Wall Imaging in Intracranial Arterial Structures in Cases with Acute or Chronic Cerebral Ischemia - Öner Özbey; Fatma Zeynep Arslan; Özdeş Mahmutoğlu; İbrahim Taşkın Rakıcı; Cem Çallı (İstanbul Medical Journal)
Introduction: We aimed to reveal the current status of high-resolution magnetic resonance imaging (HR-MRI) and its potential to identify different intracranial vessel wall pathologies. We also aimed to investigate the diagnostic performance of contrast-enhanced HR-MRI T1-SPACE sequence in determining vessel wall pathologies and to determine its contribution to conventional methods. Methods: We retrospectively reviewed HR-MRI images of 33 consecutive patients with 30% or above stenosis based on clinical, digital subtraction angiography (DSA), computed tomography angiography (CTA), and magnetic resonance angiography (MRA) evaluations. All patients had a history of stroke, and 33 stenotic vessel segments in anterior-posterior circulation were reviewed. On HR-MR images, plaque eccentricity, presence or absence of intraplaque hemorrhage, contrast enhancement pattern, and plaque length were evaluated. As causes of atherosclerosis, the presence of diabetes mellitus, hemoglobin A1c, total cholesterol, trigylicerid, and high-density lipoprotein levels, history of smoking, history of taking statin drugs, and hemoglobin levels were acquired, and the correlation between these variables and plaques labeled as stable or unstable in these patients was investigated. Results: Atherosclerosis was observed in 29 of the 33 cases included in our study, and stenosis in intracranial vascular structures due to moyamoya disease was observed in 4 cases. In patients with intracranial stenosis secondary to moyamoya disease, diffuse concentric homogeneous enhancement was observed within the vessel wall in the prestenotic artery segment. In patients with stenosis due to atherosclerosis, increased heterogeneous enhancement was observed within the atheroma plaque. A significant correlation was observed between eccentric-concentric plaque and atherosclerotic segment length. Conclusion: The vessel lumen can be evaluated using CTA, MRA, and DSA, but the vessel wall cannot be evaluated using these traditional techniques. Vessel wall imaging is helpful for identifying atheromas in intracranial and cervical carotid arteries, and for determining the morphologies of vessel walls and the surrounding structures.